Video Lirik Berbasis Animasi Pada Lagu “Bad Habbit From Habbit” Band Wakas Kota Padang - Muhammad Khalif; Dini Faisal (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The objective of designing an animated music video for Wakas Kota Padang's "Bad Habit from Habit" song is to provide a medium of communication for the song's story, meaning, and message to its audience. The design process employs the 4-D Model, which consists of four stages: define, design, develop, and disseminate. Data analysis uses the SWOT method to gather necessary data according to the design requirements. The main medium for the video is animation, supported by additional media such as posters, Instagram reels, Instagram feed, zines, t-shirts, and stickers. The results of the video's usability test on "Bad Habit from Habit" by Wakas Kota Padang, conducted among 10 participants consisting of 2 animators, 3 students of visual communication, and 5 target audience members aged 17-30, received overwhelmingly positive responses, appreciation, and audience interest. Therefore, it can be concluded that the usability of the animated music video for "Bad Habit from Habit" by Wakas Kota Padang is suitable and worthy of publication.